Procalcitonin as a Biomarker of Bacterial Infection in Sickle Cell Vaso-Occlusive Crisis - Patel, Dilip Kumar (Università Cattolica del Sacro Cuore, 2014)
Sickle cell anaemia (SCA) patients with vaso-occlusive crisis (VOC) have signs of inflammation and it is often difficult to diagnose a bacterial infection in them. This study was undertaken to evaluate the role of serum procalcitonin (PCT) as a biomarker of bacterial infection in acute sickle cell vaso-occlusive crisis. Hundred homozygous SCA patients were studied at Sickle Cell Clinic and Molecular Biology Laboratory, V.S.S. Medical College, Burla, Odisha, India. All the patients were divided into three categories namely category-A (VOC/ACS with SIRS but without evidence of bacterial infection - 66 patients), category-B (VOC/ACS with SIRS and either proven or suspected bacterial infection - 24 patients) and category-C (SCA patients in steady state without VOC/ACS or SIRS - 10 patients). Complete blood count, C-reactive protein (CRP) estimation and PCT measurement were done in all the patients. There was no significant difference in TLC and CRP values between category-A and B. In category-A, the PCT level was <0.5 ng/mL in 83.3% and 0.5–2 ng/mL in 16.7% of cases. In category-B, all the patients had PCT value >0.5 ng/mL with 87.5% of patients having >2 ng/mL. In category-C, PCT value was <0.5 ng/mL. PCT had a high sensitivity (100%) and negative predictive value (100%) for bacterial infection at a cutoff value of 0.5 ng/mL; whereas the specificity is excellent at a cut-off value of 2 ng/mL. SCA patients with VOC/ACS and SIRS having a PCT level of <0.5 ng/mL have a low probability of bacterial infection whereas PCT value of >2 ng/mL is indicative of bacterial infection necessitating early antimicrobial therapy.